Role of extracellular matrix proteins in heart function - Pelouch, Václav; Dixon, Ian M; Golfman, Leonard; Beamish, Robert E; Dhalla, Naranjan S (Molecular and cellular biochemistry, 1993)
The cardiac interstitium is populated by nonmyocyte cell types including transcriptionally active cardiac fibroblasts and endothelial cells. Since these cells are the source of many components of the cardiac extracellular matrix, and because changes in cardiac extracellular matrix are suspected of contributing to the genesis of cardiovascular complications in disease states such as diabetes, hypertension, cardiac hypertrophy and congestive heart failure, interest in the mechanisms of activation of fibroblasts and endothelial cells has led to progress in understanding these processes. Recent work provides evidence for the role of the renin-angiotensin-aldosterone system in the pathogenesis of abnormal deposition of extracellular matrix in the cardiac interstitium during the development of inappropriate cardiac hypertrophy and failure. The cardiac extracellular matrix is also known to change in response to altered cardiac performance associated with post-natal aging, and in response to environmental stimuli including intermittent hypoxia and abnormal nutrition. It is becoming clear that the extracellular matrix mainly consists of molecules of collagen types I and III; they form fibrils and provide most of the connective material for typing together myocytes and other structures in the myocardium and thus is involved in the transmission of developed mechanical force. The data available in the literature support the view that the extracellular matrix is a dynamic entity and alterations in this structure result in the development of heart dysfunction.
Keywords: Heart Failure; Collagen; Extracellular Matrix Proteins; Heart; srdce; kardiomegalie; lidé; srdeční selhání; Cardiomegaly; kolagen; chemická frakcionace; elastin; Chemical Fractionation; extracelulární matrix - proteiny; Glycosylation; glykosylace; Elastin; Humans